Capacity Enhancement in 60 GHz Based D2D Networks by Relay Selection and Scheduling - Waheed ur Rehman; Tabinda Salam; Jin Xu; Xiaofeng Tao (International Journal of Antennas and Propagation)
Millimeter-wave or 60 GHz communication is a promising technology that enables data rates in multigigabits. However, its tremendous propagation loss and signal blockage may severely affect the network throughput. In current data-centric device-to-device (D2D) communication networks, the devices with intended data communications usually lay in close proximity, unlike the case in voice-centric networks. So the network can be visualized as a naturally formed groups of devices. In this paper, we jointly consider resource scheduling and relay selection to improve network capacity in 60 GHz based D2D networks. Two types of transmission scenarios are considered in wireless personal area networks (WPANs), intra and intergroup. A distributed receiver based relay selection scheme is proposed for intragroup transmission, while a distance based relay selection scheme is proposed for intergroup transmission. The outage analysis of our proposed relay selection scheme is provided along with the numerical results. We then propose a concurrent transmission scheduling algorithm based on vertex coloring technique. The proposed scheduling algorithm employs time and space division in mmWave WPANs. Using vertex multicoloring, we allow transmitter-receiver (Tx-Rx) communication pairs to span over more colors, enabling better time slot utilization. We evaluate our scheduling algorithm in single-hop and multihop scenarios and discover that it outperforms other schemes by significantly improving network throughput.